DAMPAK KERJASAMA IESF (INTERNATIONAL ESPORTS FEDERATION) DENGAN IESPA (INDONESIA ESPORTS ASSOCIATION) TERHADAP PERKEMBANGAN ESPORTS DI INDONESIA - Fairuz, Ahmad Garibaldi Nurel; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The focus of this paper is to explain the impact of the IESF and IESPA collaboration on the development of esports in Indonesia. Esports is one of the upgrades in the field of sports. The rapid development of esports nowadays makes Indonesia cooperate with the aim of making structured developments in the field of esports in Indonesia. IESPA, which is the central organization of esports in Indonesia, has finally collaborated with IESF as an international organization in the field of esports.            This paper uses a pluralism perspective that focuses on the individual level of group analysis and international cooperation theory. By using the theory of international cooperation, this study aims to reveal the impact of IESF's collaboration with IESPA on the development of esports in Indonesia            This study shows that IESPA and the Indonesian government have a strong commitment to develop and advance esports in Indonesia through the collaboration formed with IESF. This is shown by collaborations such as joining IESPA to become a member of IESF, media consultants, event consultants and esports legalization. In the end, after the collaboration process, the impact felt by Indonesia in the development of esports was the full support of the government, normalization of esports in the community, and active participation by the community. Keywords: Partnership, IESF, IESPA, Esports